Mass Spectrometry Data Analysis in Proteomics - Matthiesen, Rune; Ed (Humana Press, 2007)
This is an in-depth guide to the theory and practice of analyzing raw mass spectrometry (MS) data in proteomics. General guidelines for data analysis using search engines such as Mascot, Xtandem, and VEMS are provided, with specific attention to identifying poor quality data and optimizing search parameters.